Development and Validation of LC Method for the Diclofenac Sodium Release Determination Using Accuracy Profile Concept - Amood AL-Kamarany, M.; EL Karbane, M.; Belomaria, M.; Azougagh, M.; Hubert, Ph.; Alanazi, F.; Cherrah, Y.; Bouklouze, A. (Asian Journal of Chemistry, 2012)
The article presents a rapid and sensitive RP-HPLC method with UV detection, using the diclofenac sodium release determination in solid pharmaceutical formulations. A novel validation strategy based on accuracy profiles was used to select the most appropriate regression model with highest accuracy within well defined acceptance limits. Furthermore, the strategy was used to determine the limits of quantification as well as the suitable concentration range. The validation phase was completed by investigating of the risk profiles of various acceptable regression models in order to avoid obtaining measurements outside the acceptance limits fixed a priori. On the other hand, the present study shows how the LC method can be used more accurately to assess the kinetic dissolution profiles, instead the UV-visible method required by monographs of the USP. Robustness study was also performed in order to demonstrate the capability of this method to remain unaffected by a small and deliberate variation in method parameters. The LC method was validated using the total error approach, as a decision tool, guarantees that each of the future results that will be within the acceptance limits settled at ± 5 %. The UV spectrophotometric method based on the USP monograph, gives rise of impurities from diclofenac sodium in acidic condition (HCl 0.1 N). These impurities absorb at the same wave length (276 nm) as the active principal ingredient, which will yield some significant error in the per cent release during the dissolution test study. Described analytical method is a simple, sensitive, specific and more accurate indicating that this LC method is useful for manufacturing and quality control assay.